2009
DOI: 10.1111/j.1600-0625.2008.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive woolly hair with hypotrichosis caused by a novel homozygous mutation in the P2RY5 gene

Abstract: During the last decade, several causative genes for hereditary hair diseases have been identified, which have disclosed the molecular mechanisms involved in hair follicle morphogenesis and cycling. We and others recently reported that mutations in the P2RY5 gene, encoding an orphan G protein-coupled receptor, underlie autosomal recessive woolly hair and/or hypotrichosis. Although these findings clearly reveal the involvement of P2RY5 mutations in hereditary hair diseases, the clinical manifestations of P2RY5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…While several studies have now identifi ed LPA 6 mutations in hypotrichosis patients (22,188,189), there have also been reports of lipase member H (LIPH) (also known as PA-PLA 1 ␣) mutations in hypotrichosis that are associated with both a decrease in LPA production as well as reduced or abrogated LPA 6 activation in cells expressing the receptor (190,191). An additional study has demonstrated that LIPH regulates hair follicle development by modulating epidermal growth factor receptor (EGFR) signaling through a tumor necrosis factor ␣ converting enzyme and the transforming growth factor (TGF)-␣ pathway (192).…”
Section: Lpamentioning
confidence: 99%
“…While several studies have now identifi ed LPA 6 mutations in hypotrichosis patients (22,188,189), there have also been reports of lipase member H (LIPH) (also known as PA-PLA 1 ␣) mutations in hypotrichosis that are associated with both a decrease in LPA production as well as reduced or abrogated LPA 6 activation in cells expressing the receptor (190,191). An additional study has demonstrated that LIPH regulates hair follicle development by modulating epidermal growth factor receptor (EGFR) signaling through a tumor necrosis factor ␣ converting enzyme and the transforming growth factor (TGF)-␣ pathway (192).…”
Section: Lpamentioning
confidence: 99%
“…More recently, LPAR6 was shown to be a receptor for LPA, activating Gα i and Gα 12/13 G proteins, inhibiting Adenylyl cyclase, phosphorylating ERK1/2, and activating Rho GTPase (Pasternack et al, 2008;Lee et al, 2009;Pasternack et al, 2009;Yanagida et al, 2009). Little is known about the role of LPAR6 in cellular physiology except that it is required for human hair growth (Pasternack et al, 2008;Shimomura et al, 2008;Pasternack et al, 2009;Shimomura et al, 2009a). LPAR6 is expressed in the inner root sheath of hair follicles (Pasternack et al, 2008;Shimomura et al, 2008) and loss-of-function mutations in this receptor are found in families with autosomal hair defects (Pasternack et al, 2008;Pasternack et al, 2009;Shimomura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal individuals in the family showed sparse hair on the scalp, eyebrows, eyelashes, axillary and body hair, however affected individuals were having normal teeth and nails. The phenotype woolyhair has already been reported by Shimomura [14]. Until now, a different mutation has been identified in LAPR6 producing LAH3 phenotype; e.g.…”
Section: Discussionmentioning
confidence: 90%